2013
DOI: 10.1242/dev.091777
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell metabolism in tissue development and aging

Abstract: SummaryRecent advances in metabolomics and computational analysis have deepened our appreciation for the role of specific metabolic pathways in dictating cell fate. Once thought to be a mere consequence of the state of a cell, metabolism is now known to play a pivotal role in dictating whether a cell proliferates, differentiates or remains quiescent. Here, we review recent studies of metabolism in stem cells that have revealed a shift in the balance between glycolysis, mitochondrial oxidative phosphorylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
488
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(519 citation statements)
references
References 126 publications
21
488
0
3
Order By: Relevance
“…MSCs differentiating toward the adipogenic lineage are more glycolytic and need reactive oxygen species for adipogenesis, whereas MSCs differentiating toward the osteogenic lineages are more dependent on oxidative phosphorylation with increased reactive oxygen species being detrimental for de novo bone formation. 58 (2) What are the pathways that are utilized by differentiated osteoblasts to synthesize bone? TOR signaling has been shown to be important for regulating Wnt-mediated increases in glycolysis but are there other pathways?…”
Section: Resultsmentioning
confidence: 99%
“…MSCs differentiating toward the adipogenic lineage are more glycolytic and need reactive oxygen species for adipogenesis, whereas MSCs differentiating toward the osteogenic lineages are more dependent on oxidative phosphorylation with increased reactive oxygen species being detrimental for de novo bone formation. 58 (2) What are the pathways that are utilized by differentiated osteoblasts to synthesize bone? TOR signaling has been shown to be important for regulating Wnt-mediated increases in glycolysis but are there other pathways?…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, while the close similarity between iPS cell generation and the acquisition of CSC is shedding new light on the roles of bona fide oncogenes, tumor suppressor genes, transcription factors and chromatin regulators, in mediating the transition from differentiated-to-stem cell states in cancer tissues, an increasing number of experimental studies have consistently revealed that, similar to embryonic and adult stem cells, iPS cells are metabolically distinct from their differentiated counterparts. [25][26][27][28][29][30][31][32] Moreover, the precise metabolic properties of stem cells appear to be functionally relevant for stem cell identity and specification regardless of their cellular sizes or cell duplication dynamics, implicating a metabolism-centric regulation of stemness and cell fate.…”
Section: Metabolic Control Of Cancer Cell Stemness: Lessons From Ipsmentioning
confidence: 99%
“…Metabolic changes are now known to have a pivotal role in dictating whether a cell proliferates, differentiates or remains quiescent. 11 Tissue-and cell-specific metabolic pathways are tightly regulated during development and perform unique functions in specific contexts. 11 Recent findings have also shown that proliferative cells at the base of the intestinal crypt are characterized by a glycolytic metabolic phenotype, whereas differentiated cells have an oxidative phosphorylation phenotype.…”
mentioning
confidence: 99%
“…11 Tissue-and cell-specific metabolic pathways are tightly regulated during development and perform unique functions in specific contexts. 11 Recent findings have also shown that proliferative cells at the base of the intestinal crypt are characterized by a glycolytic metabolic phenotype, whereas differentiated cells have an oxidative phosphorylation phenotype. 12 The short chain fatty acid butyrate, a histone deacetylase (HDAC) inhibitor, is known to promote intestinal cell differentiation.…”
mentioning
confidence: 99%